Does computed tomography-derived volumometry and densitometry of psoas muscle really correlate with complications in rectal cancer patients after elective surgery? - Kotek, Jiri; Lochman, Petr; Hulek, Michal; Sirovy, Miroslav; Merkl, Tomas; Cermakova, Eva; Kotkova, Katerina; Paral, Jiri; Dusek, Tomas (Journal of clinical imaging science, 2024)
OBJECTIVES: Although sarcopenia is recognized as one of the risk factors for increased morbidity after resection for colorectal cancer, the question of the most appropriate way to identify and quantify it is still unresolved. MATERIAL AND METHODS: This is a retrospective unicentric study following patients undergoing elective resection of the rectum for carcinoma with available staging computed tomography (CT) of the trunk. Psoas muscle density (PMD) and its area relative to patient height psoas muscle index (PMI) at the level of inferior vertebral end plate of third lumbar vertebra (L3) were assessed using an initial staging CT scan of the trunk. Post-operative complications, evaluated according to the Clavien-Dindo classification, and blood samples on post-operative days (POD) 3 and 5 were also recorded in the study population. Patients were divided into groups with complicated and uncomplicated post-operative course, and observed parameters were then statistically compared. RESULTS: The correlation of PMI values with the development of post-operative complications was not confirmed in a data set of 206 patients. PMD values were found to be borderline statistically significant in patients with complicated post-operative course, while in the group of patients with severe complications (Clavien-Dindo III-IV), there was no statistically significant difference in PMI or PMD values. The same results were obtained when comparing patients with anastomotic leak (AL). It was confirmed that operations on the lower rectum are riskier for the development of post-operative complications. The secondary objective of our study regarding serum C-reactive protein (CRP) levels of 3rd and 5th POD gave us the answer in the form of cutoff values of 115.7 mg/L (3rd POD) and 76 mg/L (5th POD). CONCLUSION: PMD appears to be a promising tool for predicting post-operative morbidity in patients after rectal resection, but a clear consensus on the method of measurement, interpretation of results and cutoff values is needed. Lower rectal resections are burdened with a higher risk of post-operative complications, especially AL. Monitoring of CRP levels remains an important marker in the prediction of AL due to its negative predictive value.
Keywords: Complications; Psoas volumometry; Rectal cancer; Psoas densitometry; Sarcopenia